Strategi Review Mufrodat: Solusi Praktis dalam Penguasaan Kosakata Bahasa Arab di MAN 1 Probolinggo - Zuhrotunnisa, Lu Aili; Khotimah, Isnol (FONDATIA, 2025)
The integration of instructional media, interval repetition methods (drill), and role-playing strategies in Arabic language learning has been proven effective in enhancing students' vocabulary mastery. This study aims to explore students' experiences and perceptions of three primary strategies: the drill method, role-playing, and self-learning tools. A qualitative case study approach was employed at MAN 1 Probolinggo, involving 11th and 12th-grade students in the religious studies program. Data collection was conducted through in-depth interviews, document analysis, and classroom observations. The findings indicate that the drill method is effective in helping students recall and comprehend Arabic vocabulary, showing stronger retention compared to conventional methods. Meanwhile, role-playing enhances students' active participation, confidence in speaking, and ability to construct spontaneous sentences, with the majority of students demonstrating significant improvement in Arabic fluency. Additionally, the use of technology-based self-learning tools, such as educational applications and digital vocabulary flashcards, further strengthens vocabulary retention. The combination of these three methods makes the learning process more engaging, dynamic, and effective, reducing students' boredom in learning Arabic. The study's findings affirm that integrating the drill method, role-playing, and self-learning tools in Arabic language instruction can improve memory retention, structural understanding, and students' speaking skills. Therefore, the implementation of these strategies in the Arabic language curriculum is recommended to enhance learning quality and foster students' independence in mastering Arabic.